1961
DOI: 10.1084/jem.113.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular Permeability

Abstract: Although the structure of renal glomerular capillaries is now well established, little is known about the mechanisms involved in the transfer of substances across their wall from the capillary lumina to the urinary spaces. According to prevailing concepts in renal physiology, the formation of glomerular fluid takes place by passive ultrafiltration of blood plasma through a sieve-like capillary wall provided with rigid pores (1-3). An alternative view assumes that the process involved is one of diffusion across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
146
0
2

Year Published

1961
1961
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 523 publications
(163 citation statements)
references
References 29 publications
15
146
0
2
Order By: Relevance
“…Large membrane-bound vacuoles containing a high concentration of ferritin were present in mesangial and glomerular epithelial cells as well as in the basal portion of the proximal convoluted tubular cells. At these late time periods many ferritin particles were present free within the cytoplasm of these cells, an observation reported by others as well (6). The intracellular distribution of ferritin was essentially similar in control animals but the concentration of ferritin in glomerular and tubular epithelial cell vacuoles appeared to be less.…”
Section: Resultssupporting
confidence: 73%
“…Large membrane-bound vacuoles containing a high concentration of ferritin were present in mesangial and glomerular epithelial cells as well as in the basal portion of the proximal convoluted tubular cells. At these late time periods many ferritin particles were present free within the cytoplasm of these cells, an observation reported by others as well (6). The intracellular distribution of ferritin was essentially similar in control animals but the concentration of ferritin in glomerular and tubular epithelial cell vacuoles appeared to be less.…”
Section: Resultssupporting
confidence: 73%
“…Studies employing ferritin as an electron microscope tracer (4,5) have suggested that the glomerular basement membrane is the normal filtration barrier to this large protein, and that increased basement membrane permeability can account for proteinuria in experimental aminonucleoside nephrosis. In the ferritin studies only small amounts of tracer escaped into the urinary space; thus the mechanism of prorein transfer across the glomerular epithelium was not clarified.…”
mentioning
confidence: 99%
“…[5][6][7] Albumin (as well as other tracer molecules, such as ferritin) is repelled at the level of the endothelium, which argues in favour of a low GSC and-on first look-seemingly supports Comper's hypothesis that the podocyte might not have a role in proteinuria.…”
Section: Marcus J Moeller and George A Tannermentioning
confidence: 68%